2012
DOI: 10.1093/carcin/bgs020
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a-5p suppresses tumor growth in colon carcinoma by targeting DTL

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that are involved in different biological processes by suppressing target gene expression. Altered expression of miR-30a-5p has been reported in colon carcinoma. To elucidate its potential biological role in colon cancer, miR-30a-5p was overexpressed via a lentiviral vector system in two different colon cancer cell lines. This induced in both lines miR-30a-5p-mediated growth inhibition, attributable to a cell cycle arrest at the G(1) phase and an induction of apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 39 publications
6
117
1
1
Order By: Relevance
“…It was reported to be remarkably downregulated in thyroid anaplastic carcinoma compared with normal thyroid tissue, suggesting a tumor suppressive role in thyroid anaplastic carcinomas (18). Similarly, Baraniskin et al (19) reported that miR-30a-5p was able to suppress proliferation and induce apoptosis of colon carcinoma cells by inhibiting the expression of DTL, which was frequently overexpressed in colorectal cancer. On the contrary, miR-30a-5p is overexpressed in glioma tissues and cell lines when compared with normal brain tissues, and its level of expression is positively associated with tumor grade of malignancy (11).…”
Section: Discussionmentioning
confidence: 96%
“…It was reported to be remarkably downregulated in thyroid anaplastic carcinoma compared with normal thyroid tissue, suggesting a tumor suppressive role in thyroid anaplastic carcinomas (18). Similarly, Baraniskin et al (19) reported that miR-30a-5p was able to suppress proliferation and induce apoptosis of colon carcinoma cells by inhibiting the expression of DTL, which was frequently overexpressed in colorectal cancer. On the contrary, miR-30a-5p is overexpressed in glioma tissues and cell lines when compared with normal brain tissues, and its level of expression is positively associated with tumor grade of malignancy (11).…”
Section: Discussionmentioning
confidence: 96%
“…6B) as well as cell growth inhibition was clearly visible in RPE-1 cells overexpressing miR-30a, suggesting that ectopic expression of this miRNA was functional and related to the observed tumor suppression. Consequently, miR-30a has been described as a suppressor of tumor growth and inhibitor of cell migration and invasion (Baraniskin et al 2012;Cheng et al 2012;Kumarswamy et al 2012;Zhang et al 2013). Altogether, our results indicate that miR-30b/c and not other miR-30 family members are specifically involved in anoikis resistance.…”
Section: Discussionmentioning
confidence: 58%
“…S6). Using previously described lentiviral systems (Gaziel-Sovran et al 2011;Baraniskin et al 2012), miR-30a and miR-30d were overexpressed in RPE-1 cells (Supplemental Fig. S7), and pro-CASP3 depletion was checked by Western blot (Fig.…”
Section: Design and Validation Of The Processed Mirnas Expression Systemmentioning
confidence: 99%
“…Furthermore, miR-140 has been shown to be essential for normal endochondral bone development and proliferation [38], while miR-103 is linked to insulin sensitivity [39] and intestinal cell proliferation [40]. Recently, miR-30a has been found to suppress tumor growth in colon carcinoma by targeting DTL gene [41]. MiR-101b cooperates with let-7 miRNAs in tumors to inhibit cell proliferation [42], and it also participates in the FGF-2-regulated cell proliferation, migration and angiogenesis through an NDY1/KDM2B-miR-101-EZH2 pathway [43].…”
Section: Potential Marker Mirnas May Distinguish Bsc From Pscmentioning
confidence: 99%